Simultaneous determination of ten aminoglycoside antibiotics in aquatic feeds by high‐performance liquid chromatography quadrupole‐orbitrap mass spectrometry with pass‐through cleanup. Issue 3 (26th December 2019) - Lou, Xiaoyi; Tang, Yunyu; Fang, Changling; Kong, Cong; Yu, Huijuan; Shi, Yongfu; Huang, Dongmei; Guo, Yaoguang; Xiao, Dongxue
Abstract: A simple and sensitive method has been established based on pass‐through cleanup and high‐performance liquid chromatography quadrupole‐orbitrap mass spectrometry (HPLC‐Q/Orbitrap MS) for the simultaneous determination of ten aminoglycosides (AGs) in aquatic feeds. The extraction solution and cleanup procedure had been optimized, and good sensitivity, accuracy, and precision were obtained. The calibration curves of AGs were linearity ( R 2 > 0.99) in the range of 2.0 to 200 μg/L (or 5.0 to 500 μg/L). The limits of detection of AGs were between 10 and 25 μg/kg. The recoveries of AGs ranged from 74.9% to 94.3%, and the intraday and interday relative standard deviations were less than 15%. Finally, this method was successfully applied to determine ten AGs in 30 aquatic feed samples. It might be the first time to use pass‐through cleanup approach combined with HPLC‐Q/Orbitrap MS method for AGs determination in aquatic feed samples. Abstract : A simple and sensitive method has been established based on pass‐through cleanup approach combined with HPLC‐Q/Orbitrap MS method for the simultaneous determination of 10 aminoglycosides (AGs) in aquatic feeds, and the AGs residues in fish, prawn, and crab feeds have been firstly successfully tested by this determination process.